Penggunaan Aplikasi InaRisk Personal Untuk Mengetahui Kesiapsiagan Masyarakat Dalam Mitigasi Bencana Di Kabupaten Katingan: The Use of the InaRisk Personal Application to Determine Community Preparedness in Disaster Mitigation in Katingan Regency - Triyadi, Antonius; Firlianty, Firlianty; Yulianto, Santosa; Yulianti, Reri; Aguswan, Yusuf (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
In today's digital era, training and professional competency development in using mobile applications is crucial. To help the public understand their Community Preparedness Index (CSI), the government has created an application called InaRISK Personal. This online application, available for Android and iOS, provides information on the hazard level of an area and provides action recommendations for participatory anticipation. This application was developed jointly by the government and other parties experienced in disaster education in Indonesia. In its development, InaRISK Personal includes several additional features to support disaster risk reduction efforts, including vulnerability surveys and household-level preparedness. The results of this training are also expected to serve as a basis for village officials and the community regarding disaster management at the regional and village levels. Therefore, we took a role in initiating the activity